2010
DOI: 10.1007/s10763-010-9255-y
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Achievement: Is There an East Asian Model?

Abstract: ABSTRACT. The importance of motivation in learning has been widely recognized. However, due to its multidimensional and complex nature, it appears difficult to synthesize research findings on motivation across studies. Heated debates about the effects of intrinsic and extrinsic motivation on learning and their interaction have been going on since the terms started to be used. Moreover, cultural difference acts as another crucial factor in the field. Using the Trends in International Mathematics and Science Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 35 publications
(34 reference statements)
9
53
0
1
Order By: Relevance
“…The results showed that intrinsic motivation strongly influenced both initial level and growth of mathematics achievement, and extrinsic motivation influenced only the initial level of achievement. In addition, Zhu and Leung (2011) showed that extrinsic and intrinsic motivation directly affected mathematics achievement in East Asian students from Hong Kong SAR, Japan, the Republic of Korea, and Chinese Taipei, but not Singapore. Furthermore, intrinsic motivation strongly influenced mathematics achievement, and the influence of intrinsic motivation on students' achievement was higher than that of extrinsic motivation.…”
Section: Motivation and Learning In Mathematicsmentioning
confidence: 99%
“…The results showed that intrinsic motivation strongly influenced both initial level and growth of mathematics achievement, and extrinsic motivation influenced only the initial level of achievement. In addition, Zhu and Leung (2011) showed that extrinsic and intrinsic motivation directly affected mathematics achievement in East Asian students from Hong Kong SAR, Japan, the Republic of Korea, and Chinese Taipei, but not Singapore. Furthermore, intrinsic motivation strongly influenced mathematics achievement, and the influence of intrinsic motivation on students' achievement was higher than that of extrinsic motivation.…”
Section: Motivation and Learning In Mathematicsmentioning
confidence: 99%
“…Yet, the fundamental problem remains pupils' motivation to study mathematics. The education systems in East Asia, Australia, England, the Netherlands and USA are discussed by Zhu and Leung (2011) from the University of Hong Kong, specifically in regards to improving pupils' interest in math's studies. In order to succeed in their architecture studies, it is essential that students have a sound understanding of the basics of mathematics, as supported in their paper by Moratalla de la Hoz and Sanz Garcia (2010) from the University of Madrid, Spain.…”
mentioning
confidence: 99%
“…Eastern students may have different motivation patterns than western students. Extrinsic motivation can have a negative effect on western students' learning (Zhu & Leung, 2011). In contrast, extrinsic motivation can have positive effects on eastern students, since, parents usually set high expectations for their children in Asian cultures (Stevenson & Stigler, 1992).…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Further, there is a cultural difference in motivation for learning between western and eastern students. Zhu and Leung (2011) found that extrinsic motivation has a detrimental effect on western students' learning, while eastern students can benefit from both intrinsic and extrinsic motivation. Therefore, future studies on motivation should consider more possible combinations under multiple goals, multiple outcomes, and multiple pathways to learning and achievement in multiple contexts (Pintrich, 2003).…”
Section: Motivation Engagement Behaviors and Learning Outcomesmentioning
confidence: 99%